Formulation of Acne Patch from Garcinia mangostana L Peel Extract With a Combination of Chitosan Polymer and HPMC Against Propionibacterium acnes Bacteria - Ramadhani, Untia Kartika Sari (Media Farmasi Indonesia, 2024)
Garcinia mangostana or Mangosteen has main compounds derived from xanthones, one of them was alpha mangosteen known having antibacterial activity. The purpose of this study was to formulate an acne patch preparation from mangosteen peel extract with a combination of chitosan and HPMC polymer against Propionibacterium acnes bacteria. Acne patches were made by solvent evaporation by using oven at 70 ﹾC. Acne patch preparation was evaluated for physical characteristics, and tested for its antibacterial effectiveness activity. The acne patch formulation was made with the ratio of Chitosan :HPMC: mangosteen peel extract at F1 (800 mg: 400 mg: 120 mg), F2 (900 mg: 300 mg: 120 mg), F3 (800 mg: 400 mg: 240 mg), F4 (900 mg: 300 mg: 240 mg). All formulas have good organoleptic properties, thickness 0,7-0,9 mm, folding resistance>300 times, low vapor transmission rate 0,0030-0,0078 g.cm2/hour, moisture absorption capacity 13-23%, content moisture <10% and uniform active substance ingredient. The patch preparation has antibacterial effectiveness with strong inhibition in the range of 10-20 mm. F1 (800 mg: 400 mg: 120 mg) and F3 (800 mg: 400 mg: 240 mg) have the strongest inhibition with 11,2 and 11,0 mm respectively.